Students` Engagement in Learning Vocabulary with “Show and Tell” Game - Triwardani, Henni Rosa (Universitas Negeri Semarang, 2024)
Mastering vocabulary is the main point in learning English. In practice it takes a strong effort to achieve this. Show and Tell game is a method that is considered effective and helps students increase the number of vocabulary, besides that this method has the advantage of building student engagement which is an important aspect of learning in class. This is an indicator of the success of the teaching and learning process that shows active student involvement and interaction during the learning process. This study aims to determine the extent to which Show and Tell games in vocabulary learning can build student engagement. Participants as research subjects were elementary school students who participated in the community service program. The data were obtained through observation and documentation which was then processed and analyzed using statistical descriptive analysis. The results show that 75% of students motivation was good, totally 80% of students tent to ask question, 80% of students engaged discussing with peer, and 90% of students were enabled to do performance and applied their vocabulary into correct sentence. Based on the presentation above could be said students engagement was good whereas classroom atmosphere showed active and interactive.